1991
DOI: 10.1093/ptj/71.11.842
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Weight Support on Normal Human Gait: Development of a Gait Retraining Strategy

Abstract: The recovery of locomotion, following interactive training with graded weight support, in the adult spinal cat has led to the proposal that removal of body weight may be a therapeutic tool in human gait retraining. There would be benefits, however, in knowing normal responses of humans to partial weight bearing before applying this strategy to patients. In this study, 10 nondisabled male subjects walked on a treadmill while 0%, 30%, 50%, and 70% of their body weight was supported by a modified climbing harness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
122
2
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(161 citation statements)
references
References 15 publications
31
122
2
4
Order By: Relevance
“…This suggests that the increases in EMG amplitude during limb loading were not caused by stretch reflex activation. Previous studies have found that the EMG amplitude increases in proportion to lower limb loading in nondisabled and spinal cord-injured humans, 4,[16][17][18] but those studies have examined normal bilateral stepping where the limb undergoes considerable flexion and extension with each step.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the increases in EMG amplitude during limb loading were not caused by stretch reflex activation. Previous studies have found that the EMG amplitude increases in proportion to lower limb loading in nondisabled and spinal cord-injured humans, 4,[16][17][18] but those studies have examined normal bilateral stepping where the limb undergoes considerable flexion and extension with each step.…”
Section: Discussionmentioning
confidence: 99%
“…Although no connection to the brain existed, this locomotor "recovery" could be amplified with treadmill training, ultimately resulting in weight-supported stepping on a treadmill [38,39]. The promising results of treadmill training in cats were soon translated to clinical applications [40], where it is now viewed as a potent therapy (reviewed in van Hedel and Dietz [41]). Although it has been argued as to whether weight-supported treadmill training is superior to weightsupported over ground locomotor training [42], it is accepted that it significantly aids rehabilitation training.…”
Section: Activity-based Approachesmentioning
confidence: 99%
“…While the conceptual framework for utilizing BWS is beyond the scope of the present discussion, at its core, unloading the paretic lower limbs allows patients with gait impairments to practice a high number of steps in a safe, controlled manner (Hidler et al [5]). Varying BWS can also be used to alter the intensity of gait therapy since unloading the patient decreases both muscle demands and, subsequently, muscle forces throughout the lower limbs [6][7][8]. This can be particularly important during the early stages of neurological injury when patients are often sick and have poor cardiovascular endurance [9].…”
Section: Introductionmentioning
confidence: 99%